Air Permeability Investigation Towards Automotive Tyre Pressure Sustainability and Life Saving - Sivarao, S.; M. J., Raguvaran; A. S., Dahlan; K., Kadirgama; M. A., Amran (Asian Research Publishing Network (ARPN), 2015)
One of the main reasons for major road accidents which often lead into loss of life's is the catastrophic tyre failure caused by vehicles running with improper tyre pressure. The phenomena where tyre loses pressure naturally and contracts over time is called air permeation, which is identified to be the main cause of tyre to deflate but rarely can be realised by naked eyes. Properly inflated tyres can safe tyre life up to 20% which is equivalent to nine months of its life span, save fuel from 4% to 10%, increase braking efficiency up to 20%, lightens steering system and ease selfsteer. Therefore, this paper reveals the investigation findings by analysing the factors that affect the air permeation that eventually causes pressure loss in an automotive tyre. The experimentations were performed in both static and dynamic conditions where they were also tested with and without loaded situation to extract precise data of the pressure loss from tyre. The results show that no matter what type of tyre or condition it undergoes, it still experience pressure drop but at different rate subjected to air properties, temperature, tyre materials and mechanical fittings of the wheel. © 20062015 Asian Research Publishing Network (ARPN).